Effectiveness of the active senior program in preparing for physical deterioration and quality aging among pre-older adults in Prachin Buri Province, Thailand: A quasi-experimental study - Nambut, Phanutchanat; Krampaiboon, Lalisa; Konghrang, Siriporn; Khantikulanon, Nonlapan; Praserttai, Chaninan; Mungkhunthod, Sootthikarn; Tanthanapanyakorn, Phannathat (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Thailand’s rapidly aging population presents unique challenges, particularly in promoting health and well-being among pre-older adults. Physical deterioration and related health complications become increasingly prevalent in this demographic, affecting quality of life, independence, and community involvement. Preparing for deterioration and quality aging involves taking proactive steps to address the physical declines associated with aging while enhancing overall well-being. This approach helps ensure a high quality of life as individuals age, enabling them to remain active and independent during the transition to older adulthood. Objective: This study aimed to evaluate the effectiveness of the Active Senior Program in preparing for physical deterioration and enhancing the quality of aging among pre-older adults in Prachin Buri Province, Thailand. Methods: This quasi-experimental study included 80 pre-older adults aged 50 to 59 years, divided into two groups using purposive sampling: the intervention group (n = 40) and the control group (n = 40). The intervention group participated in a five-week Active Senior Program, while the control group received a self-exercise handbook. The study was conducted from August to December 2023. Assessments involved interviews and the completion of an evaluation form at baseline, post-intervention, and three-month follow-up. Data analysis was performed using descriptive statistics and a repeated-measures ANOVA test. Results: The analysis showed statistically significant differences in body mass index (F = 6.770, p = 0.011), waist circumference (F = 6.975, p = 0.011), and exercise behavior scores (F = 57.428, p <0.001) between the intervention and control groups at the three-month follow-up. Furthermore, within the intervention group, these parameters had statistically significant differences from baseline to the three-month follow-up (p <0.001). However, there were no significant differences in muscle mass observed between or within the groups. Conclusion: This study highlights the effectiveness of the Active Senior Program in promoting exercise behavior, reducing body mass index, and decreasing waist circumference among pre-older adults. Nurses are crucial in implementing and supporting such interventions within primary care. Integrating this program can foster long-term health, independence, and quality aging. Sustained collaboration between healthcare providers and policymakers is essential to ensuring its long-term success and maximizing community well-being. Trial Registry Number: Thai Clinical Trials Registry (TCTR20250217006)